PENGEMBANGAN KAWASAN AGROWISATA KEBUN BELIMBING DI KECAMATAN TAWANGHARJO, KABUPATEN GROBOGAN, PROVINSI JAWA TENGAH - Rhey Pasha Visa Sandy; Hendrawati Hamid; Hasna Azmi Fadhilah (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2021)
Tawangharjo is a sub-district that is going to be developed as a new destination of Agrotourism. This agrotourism is classified as a new type of tourism in Grobogan Regency. This study aims to determine and analyze how the development of agrotourism in Tawangharjo District, as well as to explain the inhibiting factors and efforts made by the government and local agencies in developing the agrotourism area. This study used descriptive qualitative method with an inductive approach, combined with observation, interviews, and documentation. Further, the authors analysed the data by creating a data map, exploring data presentation, comparing all data, then drawing conclusion. The results show that the indicators for the development of the Starfruit Garden Agrotourism Area, Tawangharjo Sub-district, were still not met, Amenities and Ancillary become the main problems because physical development required time and budget, while facilities were the main support for agrotourism activities. In addition, the Covid-19 pandemic has further exacerbated the situation by refocusing the budget and significantly reducing the number of tourists. The quality of human resources needs to be improved, including the managers’ capacity and the community's ability to diversify, promote, and multiply the products. As a suggestion, the Grobogan Regency government should further optimize the tourism program and policies, in order to increase production capacity and develop agrotourism facilities. Keyword: Development, Tourism, Agrotourism